Slip flow of micropolar nanofluid over a porous rotating disk with motile microorganisms, nonlinear thermal radiation and activation energy. (March 2021) - Khan, M. Ijaz; Waqas, Hassan; Khan, Sami Ullah; Imran, Muhammad; Chu, Yu-Ming; Abbasi, Aamar; Kadry, Seifedine
Abstract: A three-dimensional (3-D) investigation of micropolar nanofluid has been presented under the novel impact of nonlinear thermal radiation, activation energy and magnetohydrodynamic features. The induced flow is reflected by a rotating disk which rotates with uniform velocity along z -directions. The fundamental features of Brownian diffusion and thermophoretic assessment is determined by following Buongiorno's nanofluid model. The nanofluid contains gyrotactic microorganisms for which bioconvection pattern is examined for stability assessment. The model flow problem under the certain flow assumptions are retained into the set of dimensionless eqs. A numerical procedure is employed to achieve the solution of such equations. The prime features of parameters against velocity, temperature, concentration and microorganism profiles are graphically examined with justified physical consequences. The numerical computations for wall shear stress, effective local Nusselt number, local Sherwood number and local motile density number are elaborated in terms of numerical data. The simulated theoretical results yield dynamic applications in era of thermal engineering and bio-technology area